Directing shows and art projects: innovative strategy for the training of specialists branches of performing arts - Shumakova, Svitlana (My University, 2022)
The author touches on the topic of innovative strategies for training specialists in the field of stage arts in the context of directing shows and art projects against the background of artistic trends of the time to satisfy the artistic and aesthetic needs of the modem spectator.
Keywords: сценічне мистецтво, performing arts; освіта мистецька, art education